Damping Energy Dissipation and Parameter Identification of the Bellows Structure Covered with Elastic-Porous Metal Rubber. (22nd February 2021) - Shen, Guojian; Li, Min; Xue, Xin
Abstract : In order to improve damping energy dissipation of a U-shaped bellows structure, elastic-porous metal rubber as a cover layer was adopted and the corresponding vibration parameters were identified. First, the evolution of energy dissipation characteristics with respect to the changes of amplitude and frequency was investigated through a dynamic experimental test in the bending direction of the covered bellows structure. Second, the conspicuous hysteresis loop characteristics were described while the nonlinear constitutive relation was analytically modelled based on the exact decomposition method. Third, the corresponding parameters on dynamic properties of the covered bellows structure were determined by generalized least-squares estimation. Finally, the prediction results were compared with the measured displacement-restoring force curves to verify the accuracy of the developed dynamic model. The results indicate that the proposed dynamic model associated with the nonlinear constitutive relation for the covered bellows structure can well describe the evolution of the restoring force in terms of amplitude and frequency.